‘With this study, we have hope that something is coming’: community members’ perceptions of HIV cure-related research in Durban, South Africa – a qualitative focus group study - Karine Dubé; Deli Mthimkhulu; Wiseman Ngcobo; Deborah Mindry; Luyanda Maphalala; Vanessa Pillay; Whitney Tran; Ana Korolkova; Thumbi Ndung’u; Krista Dong (HIV Research & Clinical Practice)
Background Developing a cure for HIV remains a global scientific priority. In 2022, the Females Rising through Education, Support and Health (FRESH) cohort launched an HIV cure-related trial involving an analytical treatment interruption (ATI) in Durban, South Africa. Objectives To explore community perspectives about HIV cure-related research. Methods Between July–August 2022, we conducted three focus groups with community members. We transcribed audio recordings verbatim and used content analysis to analyze the data. Results Twenty community members (13 women and 7 men) participated in three focus groups (HIV status not included). Participants viewed HIV cure-related research as a way to address the issue of defaulting on (not taking) HIV treatment. Participants expressed hesitancy around ATIs, since these contradict longstanding treatment adherence messages. Participants shared concerns around the risk of side effects from experimental interventions balanced against potential efficacy. They advocated for trial participants to have the right to decide whether to inform their sex partners about their HIV status and ATI participation, rather than research teams making disclosure mandatory. Focus group participants also emphasized the importance of using simple language to explain HIV cure-related research. Conclusions With HIV cure trials set to launch across Africa in the future, there is a critical need to better understand and respond to local community needs and preferences and to adopt this as standard practice prior to regional trial implementation.